ยางธรรมชาติเสริมแรงด้วยซิลิกาปริมาณสูงที่เกิดขึ้นผ่านกระบวนการโซล-เจลในน้ำยาง - มันทนา ถิรกุลรติ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
In this study, the synthesis of in situ filled in natural rubber (NR) latex was investigated to find the optimum that produced high in situ silica content and good dispersion of silica particle using a sol-gel process. The effects of various parameters for the sol-gel reaction such as tetraethoxysilane (TEOS) content, mole ratio of water to TEOS, reaction time and reaction temperature on the silica content were investigated. The result shows that the optimum condition for the sol-gel reaction in NR was the use of TEOS 200 phr and mole ration water to TEOS of 28.91:1 under room temperature for 1 day. The in situ silica content was up to 53.61 phr or 34.9 %. Moreover, the effect of in situ silica on the properties (i.e. cure time, mechanical properties, dynamic properties and thermal properties) of NR vulcanizates were also investigated and compared with commercial silica filled NR vulcanizates. The properties of in situ silica filled NR vulcanizates were higher than those of NR vulcanizated with commercial silica. These unique characteristics of the in situ silica composite can be ascribed to the well dispersed in situ silica particles within the NR matrix by SEM analysis. The addition of coupling agent also improved the mechanical properties of the commercial silica composites, while in situ silica composites were not affected.